ENSURING THE INDEPENDENT LIFE OF PEOPLE WITH DISABILITIES IN A REGIONAL SOCIETY - G. Zhigunova (Вестник университета, 2018)
Ensuring the independent life of people with disabilities has been determined by the state of many factors, among which the availability of social infrastructure is crucial. To date, a regulatory framework has been developed to ensure the independent life of people with disabilities, which is implementing in measures to create an accessible environment in the constituent entities of the Russian Federation. In order to identify the level of accessibility of the social environment for persons with disabilities in the regional society, infrastructure objects of the Murmansk region have been examined. The observation method has been used, during which 323 objects were analyzed. The results of the analysis showed that today less than half of the infrastructure facilities meet the regulatory requirements for ensuring an independent life for people with disabilities.